Financial Inclusion - A Foothold on the Ladder toward Prosperity? : An Evaluation of World Bank Group Support for Financial Inclusion for Low-Income Households and Microenterprises - Independent Evaluation Group (World Bank, Washington, DC, 2021)
Access to financial services has long been believed to lift people out of poverty by allowing them to seize economic opportunities and increase their welfare. Despite rapid progress of 700 million people gaining access to formal financial services, 2 billion remain excluded. Financial inclusion -- access by poor families and microenterprises to financial services -- has been an objective of the World Bank Group for a long time, reaffirmed in 2013 by President Jim Kim’s commitment to the Universal Access Goal by 2020. This evaluation examines the relevance and effectiveness of seven years (FY07-13) of World Bank Group support to financial inclusion and its impact on the poor. It found that the World Bank Group contributed significantly to progress in financial inclusion globally and in client countries. It has “reached” a substantial share of the microfinance industry. Its support is strategically aligned with countries’ needs, focusing primarily on countries with low inclusion rates and addressing development priorities. The Bank Group has also contributed to the sustainability of microfinance services. Yet the Bank Group’s approach to identify and tackle constraints to financial inclusion at the country level is not sufficiently comprehensive. This is of particular concern for areas that are not subject to prudential regulations, like mobile money and rural savings and credit cooperatives. Even though the Bank Group was able to leverage its impact through international partnerships, these bear costs and risks and often lack results frameworks. But most importantly, the commitment to the Universal Access Goal and the resulting “push” for enabling access to financial services through transaction accounts may create a bias for driving up sheer access numbers. This may be problematic for several reasons: (i) access does not necessarily lead to inclusion, given high dormancy rates of newly created accounts; (ii) the link between access to finance and poverty alleviation is neither certain nor well understood, given the evidence that, in spite of modest benefits, the promise of microfinance pulling millions out of poverty has not been fulfilled; and (iii) current trends suggest one billion people may still lack access by 2020. These remaining financially excluded will increasingly be broadly distributed across many countries and predominantly in rural areas. Providing access to them is likely to require subsidization. Striking a balance between the costs and benefits of universal inclusion and weighing these against the cost and benefits of other competing development priorities will be essential.